The Battle of Stamford Bridge: The Reliability of the Accounts in the Kings' Sagas. - Blundell, Michael C. (Scandinavian Studies, 2024)
The Battle of Stamford Bridge, fought on September 25, 1066, was a decisive battle which involved two contenders for the English throne, Harold Godwinson of England and Harald Sigurdsson of Norway. Reconstructions of the battle rely almost entirely on accounts in original written sources, the most detailed of which are the three major saga compendia, Morkinskinna, Fagrskinna , and Heimskringla. Saga accounts of the battle have often been considered to be unreliable and of little value as historical sources based primarily on their dates of composition, their reliance on oral traditions as source material, and their inclusion of certain elements, such as English cavalry charges. This article examines the possibility that several passages in the Morkinskinna, Fagrskinna , and Heimskringla accounts in fact provide reliable information that can be used for reconstructions of the battle. The criticisms mentioned above are examined for their validity as determining factors for judging the reliability of specific saga passages. Information gathered from saga and memory studies is used to argue that core information passed on in oral traditions and used by the authors of the kings' sagas was likely reliable, even after 150 years of retellings. Also reviewed for reliability are several saga passages that contain information which is corroborated by English and/or Anglo-Norman accounts. Additionally, comparisons of the saga accounts with English and Anglo-Norman accounts combined with data from tactical and logistical analyses are used to demonstrate both the plausibility and likely reliability of additional saga passages.